Oil-in-water type emulsifier, emulsion suspension using the same, and method for producing emulsion suspension
Unmodified cellulose nanofibers with specific diameter ranges, regenerated from modified cellulose, serve as effective oil-in-water emulsifiers, overcoming limitations of existing technologies by providing stable and versatile emulsification of diverse oily substances.
Patent Information
- Application Number
- JP2023147572
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-25
AI Technical Summary
Existing cellulose nanofibers, both mechanically defibrated and modified, have limitations in their ability to act as effective surfactants, particularly in terms of stability and versatility in emulsifying various oily components.
The use of unmodified cellulose nanofibers with an average fiber diameter of 3 nm to 10 nm as an oil-in-water emulsifier, which are regenerated from modified cellulose with functional groups removed, allowing for broader compatibility with different oily substances without the need for additional surfactants.
This approach achieves a stable emulsification state with a small amount of cellulose nanofibers, allowing for the emulsification of various oily substances, including those with slightly hydrophilic properties, without stability issues or the need for additional surfactants.
Smart Images

Figure 2025040651000003 
Figure 2025040651000004 
Figure 2025040651000005
Abstract
Description
[Technical field]
[0001] This invention relates to the use of cellulose nanofibers as an emulsifier. [Background technology]
[0002] Hydrophilic liquids with high polarity such as water and lipophilic liquids with low polarity, sometimes referred to as oil, do not mix as is. However, there is a demand for mixing these in various fields, including medicine and cosmetics. In many cases, surfactants are added to stabilize the mixture through emulsification, which disperses tiny droplets of water or oil in the other liquid. In particular, oil-in-water (O / W) emulsions, in which oil droplets are dispersed in water, are used in topical skin preparations and cosmetics.
[0003] However, many of the surfactants that have been used in the past are derived from petroleum-based materials that are difficult to decompose, and have sometimes been viewed as problematic in terms of environmental impact. Therefore, the use of materials composed of natural raw materials as surfactants has been considered. Among natural raw materials, cellulose is said to exhibit amphiphilicity because it has both hydrophilic OH groups and hydrophobic CH groups (Non-Patent Document 1), and the use of cellulose as a surfactant has been proposed.
[0004] For example, Patent Document 1 proposes a method for obtaining an organic cosmetic preparation in which olive oil is dispersed in water using cellulose nanofibers with an average fiber diameter of 10 to 50 nm, which are obtained by mechanically defibrating unmodified cellulose, as an emulsifier.
[0005] Furthermore, if a surfactant is included, it may cause stickiness, which may reduce the feeling of use in cosmetics, etc. As a means to solve this problem, Patent Document 2 proposes cellulose nanofibers having a phosphate group or a functional group derived therefrom as an O / W type emulsifier. It is reported that stickiness can be prevented by stably emulsifying a mixed liquid containing water and glycerin in the water phase using squalane or the like in the oil phase.
[0006] Furthermore, in order to avoid limitations on the oily components contained in cosmetics, Patent Document 3 describes a means of stabilizing the emulsion state by adding unmodified mechanically defibrated cellulose nanofiber as an emulsion stabilizer in addition to the emulsifier.
[0007] Furthermore, Patent Document 4 describes an example in which spherical cellulose fine particles having an aspect ratio of 1.3 or less are used in a water-in-oil (W / O) emulsion composition.
[0008] Furthermore, Non-Patent Document 2 reports that TEMPO-oxidized cellulose nanofibers, which are carboxy-modified cellulose nanofibers, are adsorbed onto the surfaces of oil droplets to form stable emulsions (Pickering emulsions). [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Patent No. 6360408 [Patent Document 2] Patent No. 7220088 [Patent Document 3] Patent Publication No. 2021-59502 [Patent Document 4] JP 2006-342140 A [Non-patent literature]
[0010] [Non-Patent Document 1] Keita Sakakibara, "Cellulose nanofiber", Molding and Processing, Vol.30(8), p.424-428 (2018) [Non-Patent Document 2] Yosuke Ushiroi: "Pickering emulsion technology and stabilization using cellulose nanofibers", The forefront of cellulose nanofiber research and practical applications, NTS Co., Ltd., p.700-705 (2021) Summary of the Invention [Problem to be solved by the invention]
[0011] However, the reported mechanically defibrated cellulose nanofibers and modified cellulose nanofibers sometimes did not fully exert their surfactant effects.
[0012] Specifically, in modified cellulose nanofibers such as the phosphoric acid modified cellulose nanofiber described in Patent Document 2 and the TEMPO oxidized cellulose nanofiber described in Non-Patent Document 2, interactions occur between the introduced functional groups and oily substances, so there are limitations on the types of oily components that can be emulsified. Furthermore, in the proposal of Patent Document 3, the cellulose nanofiber is an emulsion stabilizer and requires a separate emulsifier, so the emulsifier could not be replaced with the cellulose nanofiber. In addition, when using the cellulose microparticles described in Patent Document 4, the specific surface area is too small due to the small aspect ratio of 1.3 or less, so a large amount must be added to surround the water droplets in the oil.
[0013] Therefore, the object of this invention is to provide an emulsifier using cellulose nanofibers that has fewer restrictions on the type of oil phase and that achieves a sufficiently stable emulsified state with a small amount. [Means for solving the problem]
[0014] The present invention solves the above problems by providing an oil-in-water emulsifier that is unmodified cellulose nanofibers having an average fiber diameter of 3 nm or more and 10 nm or less.
[0015] With mechanical fiberization, the achievable fiber diameter is too large, so a large amount of cellulose nanofibers is required to stably surround the oil droplets, but by narrowing the average fiber diameter to the above range, stable emulsification is possible with a small amount. Furthermore, by making the cellulose nanofiber unmodified, even oily substances that are somewhat hydrophilic, such as fatty acids, can be emulsified, and the range of applicable oily substances is wider than when modified cellulose nanofibers are used, realizing high versatility.
[0016] The oil-in-water emulsifier according to the present invention may be configured such that the unmodified cellulose nanofiber is regenerated cellulose regenerated from modified cellulose into which functional groups have been introduced. If the cellulose nanofiber is left unsubstituted without functional groups, it is difficult to achieve the above average fiber diameter even if it is defibrated, but by first introducing functional groups to form modified cellulose, defibrating the cellulose, and then regenerating the modified cellulose to form unmodified cellulose, not only can the above average fiber diameter be achieved, but also the limitations caused by the interaction between the oily substance and the functional groups during emulsification can be avoided, realizing high versatility.
[0017] The oil-in-water emulsifier of the present invention can be used to produce an emulsified suspension in which oil droplets are dispersed in water. Effect of the Invention
[0018] By using the oil-in-water emulsifier of the present invention, since unmodified cellulose molecules do not have any extra functional groups that inhibit emulsification, the balance between hydrophilicity and hydrophobicity is not biased, and various oily substances can be emulsified without the use of other surfactants. In addition, an emulsified suspension once emulsified with the oil-in-water emulsifier of the present invention can stably maintain its dispersed state for a long period of time. Since unmodified cellulose itself does not have functional groups, it has little effect on the emulsified oily substances, and the emulsion state can be kept stable throughout the cellulose nanofibers. [Brief description of the drawings]
[0019] [Figure 1] A diagram showing the contact angle θ between the water phase, the oil phase, and the solid particles. [Diagram 2] Photographs showing the difference in emulsification state between Example 1 and Reference Example 1 [Diagram 3] (a) A digital microscope photograph of the emulsified suspension of Example 1 at a magnification of 500 times. (b) A digital microscope photograph of (a) at a magnification of 1,000 times. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention is described in detail below. The present invention relates to an oil-in-water emulsifier that is unmodified cellulose nanofiber, an emulsified suspension using the same, and a method for producing the same.
[0021] Cellulose nanofibers (hereinafter abbreviated as "CNF") are made by processing cellulose materials into fine fibers. The unmodified cellulose nanofibers (hereinafter abbreviated as "unmodified CNF") used in this invention are CNFs that have no or can be considered to have no modification due to functional groups in the molecular structure of cellulose. They can be CNFs that are mechanically defibrated directly from cellulose materials, leaving the molecular structure of cellulose unchanged, or CNFs that have had part of the molecular structure of cellulose chemically modified and then defibrated to regenerate cellulose. However, it is preferable that the cellulose that has been chemically modified once is regenerated to a degree that can be considered to be unmodified by removing the functional groups that have been introduced.
[0022] Examples of modified cellulose that can be modified and then regenerated back to unmodified cellulose include phosphorylated cellulose, which is obtained by adding carbon disulfide to alkali-treated cellulose to form xanthate groups (-OCSS), and cellulose that is obtained by adding carbon disulfide to alkali-treated cellulose. - M +Examples include xanthate cellulose, which is a compound that has been introduced with cellulose nitrile. Chemically modifying cellulose materials such as pulp makes it easier to create nanofibers than defibrating the cellulose materials as is. CNF that has been chemically modified and defibrated in this way is called "modified CNF." CNF obtained by a regeneration process in which functional groups are removed from the molecular structure of the chemically modified cellulose in modified CNF and the cellulose is returned to its original state is called "regenerated CNF." Hereinafter, when simply referring to CNF, this includes not only unmodified CNF (including regenerated CNF) but also modified CNF.
[0023] Among the regenerated CNFs, not only those in which all of the hydroxyl groups once modified to other functional groups such as xanthate groups have been returned to the original hydroxyl groups, but also those in which a very small amount of some of the functional groups remain as other functional groups may be included. Specifically, it is preferable that the amount of modified cellulose units among all cellulose units is 0.1% or less, more preferably 0.01% or less, and particularly preferable that it is below the detection limit and can be considered as 0. Furthermore, these regenerated CNFs may be purified before use if necessary.
[0024] The number average fiber diameter of the unmodified CNF used in this invention must be 3 nm or more. The present invention can be carried out with a diameter smaller than this, but to make it less than 3 nm requires a lot of energy and is not very practical in terms of work efficiency. On the other hand, the number average fiber diameter of the unmodified CNF must be 10 nm or less. If it exceeds 10 nm, the specific surface area will be small, and a large amount of unmodified CNF may be required to surround the surface of the oil droplets and emulsify them.
[0025] The average aspect ratio of the unmodified CNF used in this invention is preferably 100 or more and 300 or less. If it is less than 100, the length of the unmodified CNF is insufficient, and there is a strong tendency for the stabilization of the emulsified state to be difficult to be fully exhibited. Even if the average aspect ratio is large and exceeds 300, it will contribute to the stability of the emulsified state if it is practical, but the viscosity of the emulsified suspension will increase, making actual production difficult.
[0026] CNF forms an emulsified suspension called a Pickering emulsion by adsorbing to the periphery of oil droplets in a hydrophilic solvent such as water, and the unmodified CNF of this invention is similar. A Pickering emulsion is an emulsion stabilized by the adsorption of solid particles to the liquid-liquid interface, and is formed when the wettability of the solid particles to the two liquids is appropriate. Figure 1 shows a schematic diagram of the formation of a Pickering emulsion. A solid particle 13 exists between an aqueous phase 11 and an oil phase 12, and the contact angle between the three phases, which is the angle between the tangent L of the solid particle 13 surface at the interface between these phases and the interface P, is θ. The adsorption energy E required to separate a solid particle once adsorbed to an oil droplet from the liquid-liquid interface is calculated by the particle size R of the solid particle and the interfacial tension γ of the liquid-liquid interface. wo and is expressed by the following formula (1): The larger this E is, the more difficult it is for solid particles to detach, and the easier it is for them to stably adsorb and form an emulsion.
[0027] E=πR 2 Gamma wo (1-cosθ) 2 (1)
[0028] The contact angle θ between the three phases is thought to be different between modified CNF with functional groups and unmodified CNF of the present invention that does not have functional groups. In modified CNF, the introduction of functional groups with high polarity promotes hydrophilization, so the contact angle θ becomes smaller, and the adsorption energy E also becomes smaller according to the above formula (1). In other words, it becomes unstable. The unmodified CNF used in the oil-in-water emulsifier of the present invention has a larger contact angle θ than the modified CNF. Therefore, even under conditions where the emulsion is not stable with modified CNF, the unmodified CNF can maintain a stable Pickering emulsion.
[0029] In addition, CNFs, including unmodified CNFs, form a network structure by interacting with each other when in water at a certain concentration or higher. It is believed that the oil droplets of a Pickering emulsion, once formed, are stabilized for a long period of time by this CNF network structure.
[0030] The aqueous phase may contain water-soluble substances other than water, as long as the effects of the present invention are not impaired. Examples of water-soluble substances include, but are not limited to, diols, glycerin, sugars, salts, pH adjusters, preservatives, etc.
[0031] On the other hand, as the hydrophobic liquid corresponding to the oily substance that becomes the oil droplets, the more stably it can be used, the more lipophilic the liquid with a small polarity. As the oily substance that can be used, not only non-polar hydrocarbons such as hexane, cyclohexane, benzene, toluene, and squalane, but also liquids with partial polarity such as terpenes such as limonene, alcohols with 4 or more carbon atoms, and fatty acids with 4 or more carbon atoms can be used. Since the oil-in-water emulsifier according to the present invention has a high performance of stabilizing Pickering emulsions as described above, it is possible to form a stable Pickering emulsion even with slightly hydrophilic liquids such as alcohols with 10 to 20 carbon atoms such as 1-decanol (C10) and ricinoleic acid (C18) and fatty acids. In addition, silicone oil, olive oil, and the like, which are more hydrophobic, can be used, but are not limited to these. Only one type of oily substance may be used, or two or more types may be mixed and used.
[0032] Oily substances that can be used in this invention can be used if their HLB value is 7.5 or less. If it exceeds 7.5, the polarity is too high and emulsification becomes difficult even with unmodified CNF. However, oily substances with a low HLB value can be used without any problems, even if it is 0.
[0033] The content ratio of unmodified CNF used for the oil-in-water emulsifier of the present invention depends on the polarity of the oily substance used, but it is preferable that the mass ratio of oily substance:unmodified CNF is in the range of 10:1 to 200:1 because a Pickering emulsion can be stably formed. If the content ratio of unmodified CNF is high, the viscosity becomes too high and emulsification cannot be performed well, which is not economically preferable. Also, if the amount of unmodified CNF added is small, there is a risk that the unmodified CNF will not be enough to surround the surface of the oil droplets, and emulsification will not be possible.
[0034] In addition, the mass ratio of the aqueous phase and the oily substance that can be emulsified as an oil-in-water emulsifier is preferably 19:1 to 1:1 because it can stably form a Pickering emulsion. If the amount of the oily substance is less than this, the oil droplets themselves are stable, but there is too little to make an emulsion, so there is little benefit to adding it. If the amount of the aqueous phase is less than this, there is a risk that the oil droplets are too many and it is not possible to sufficiently form a Pickering emulsion.
[0035] When the size of the oil droplets in the emulsified suspension formed by the oil-in-water emulsifier according to the present invention is about 10 μm or more and 30 μm or less, it can be said that the Pickering emulsion is stable.
[0036] The emulsification method using the oil-in-water emulsifier of this invention is not particularly limited in terms of the order or procedure of addition, but for example, unmodified CNF can be added to a liquid in a two-layer state in which the aqueous phase and the oily substance are layered, and the liquid can be mechanically stirred with a homogenizer or the like to break the oily substance into fine oil droplets and emulsify the unmodified CNF by adsorbing it to the surface of the oil droplets. EXAMPLES
[0037] The following describes specific examples of the present invention. First, as a preliminary step to obtaining unmodified CNF, xanthated CNF is produced, and unmodified CNF, which is regenerated CNF, is obtained as regenerated cellulose by removing the xanthate group from the xanthated CNF.
[0038] (Sample 1: Preparation of unmodified CNF) The following materials were used for producing xanthate-conjugated CNF: Kraft pulp (manufactured by Nippon Paper Industries Co., Ltd.: NBKP, α-cellulose content: 90% by mass) hereinafter referred to as "NBKP".
[0039] <Alkaline treatment> NBKP was weighed out so that the pulp solids (pulp solids are the amount excluding the water content in the pulp; the same applies below) was 100 g. 2,500 g of an 8.5% by mass aqueous sodium hydroxide solution was added thereto, and the mixture was stirred at room temperature for 3 hours to carry out an alkali treatment. The pulp after this alkali treatment was subjected to solid-liquid separation using a centrifugal dehydrator (Kokusan Co., Ltd., H-110A, filter cloth 400 mesh) to obtain a dehydrated alkali cellulose. The sodium hydroxide content in this dehydrated alkali cellulose was 7.5% by mass, and the pulp solids content was 27.4% by mass.
[0040] <Xanthate treatment> The dehydrated alkali cellulose prepared above was weighed out so that the pulp solid content was 100 g. 35 g of carbon disulfide (35% by mass relative to the pulp solid content) was added thereto, and the sulfurization reaction was allowed to proceed at room temperature for 4.5 hours to perform a xanthate treatment, thereby obtaining xanthate cellulose.
[0041] <Defibrillation processing> The xanthated cellulose prepared by the above xanthation treatment was weighed out so that the pulp solid content was 100 g, and distilled water was added to disperse the xanthated cellulose so that the pulp solid content concentration was 5% by mass. While centrifuging using the centrifugal dehydrator, distilled water was poured over the xanthated cellulose to thoroughly wash it, removing impurities, alkali, unreacted carbon disulfide, etc. All of the xanthated cellulose after washing was collected, and distilled water was added to make a 20 kg aqueous suspension with a cellulose content concentration (hereinafter referred to as "cellulose concentration") of 0.5% by mass. This aqueous suspension was defibrated by passing it through a high-pressure homogenizer (manufactured by Sanwa Engineering Co., Ltd., H20 type) a total of 5 times at a flow rate of 2.5 L / min and a pressure of 40 MPa to obtain xanthated CNF.
[0042] <Recycling and redispersion processing> To 16.4 kg of the aqueous suspension of zanthated CNF (cellulose concentration: 0.5% by mass) obtained by the above procedure, 360 ml of 1 M sulfuric acid aqueous solution was added, and the mixture was stirred with an agitator for 1 hour for regeneration treatment. After the treatment, it was neutralized with 1 M sodium hydroxide aqueous solution to obtain a regenerated CNF aqueous suspension. When the average degree of zanthate substitution of the regenerated CNF (hereinafter referred to as "RCNF") was measured, it was less than 0.001, which is the lower limit of measurement. Thus, it was confirmed that the zanthate groups were almost completely eliminated by the acid treatment and returned to hydroxyl groups.
[0043] <Measurement of degree of zanthate substitution> The average degree of zanthate substitution of RCNF was measured by the Bredee method. The degree of zanthate substitution is a value for the degree to which zanthate groups are introduced per glucose unit of cellulose. The procedure of the Bredee method was as follows. 40 g of the above RCNF aqueous suspension was weighed, 50 mL of 0.5 M sodium hydroxide aqueous solution (5 °C) was added and stirred. After standing for 15 minutes, it was neutralized with 1.5 M acetic acid aqueous solution. 100 mL of distilled water was added thereto and stirred well, and 10 mL of 1.5 M acetic acid aqueous solution and 10 mL of 0.05 mol / L iodine aqueous solution were added. This solution was titrated with 0.05 mol / L sodium thiosulfate aqueous solution, and the degree of zanthate substitution was calculated from the following formula (2) based on the titration amount of sodium thiosulfate aqueous solution and the cellulose content in the sample.
[0044] Degree of zanthate substitution = (0.05 × 10 × 2 - 0.05 × titration amount of sodium thiosulfate (mL)) ÷ 1000 ÷ (cellulose content in sample (g) / 162.1)......(2)
[0045] While centrifuging the RCNF aqueous suspension obtained above using the above centrifuge, distilled water was added and washed thoroughly. All of the washed RCNF was recovered, and distilled water was added to make 8 kg of an aqueous suspension with a CNF concentration of 1.0% by mass. This aqueous suspension was redispersed by passing it through the high-pressure homogenizer three times at a flow rate of 2.5 L / min and a pressure of 40 MPa.
[0046] <Measurement of fiber diameter and fiber length of CNF> A water suspension of RCNF diluted with distilled water to a cellulose concentration of 0.01% by mass was dyed and dried on a support film to prepare a dried specimen. The specimen was observed using a field emission scanning electron microscope (FE-SEM, Hitachi High-Tech Corporation, S-4800) at an accelerating voltage of 25 kV. The fiber diameter and fiber length were measured from 50 randomly selected nanofibers from the 130,000x magnification image and the 25,000x magnification image, respectively. The fiber diameter was 3.9 nm to 9.7 nm, and the number average fiber diameter was 6.4 nm. The fiber length was 394 nm to 1.04 μm, and the number average fiber length was 717 nm. The average aspect ratio calculated from the number average fiber diameter and number average fiber length was 113. The physical properties of each CNF are summarized in Table 1 below.
[0047] [Table 1]
[0048] (Sample 2: Mechanically defibrated CNF) BiNFi-s manufactured by Sugino Machine Co., Ltd. was used as the CNF obtained by mechanical fiberization. The fiber diameter and fiber length were measured in the same manner as in Sample 1, and the fiber diameter was in the range of 24.1 to 53.2 nm, the number average fiber diameter was 31.2 nm, the fiber length was in the range of 1.1 to 3.2 μm, and the number average fiber length was 2,215 nm. The average aspect ratio calculated from these was 71.
[0049] (Sample 3: phosphorylated CNF) The modified CNF used was phosphorylated CNF, which was produced as follows. 18g of ammonium dihydrogen phosphate and 48g of urea were dissolved in 60g of distilled water to obtain a phosphorylation reagent. 10g of NBKP was collected in a tray on an absolute dry basis and uniformly impregnated with 31.5g of phosphorylation reagent. The tray was placed in a 165°C constant temperature incubator (Yamato Scientific Co., Ltd.: DKN602) and dried for 30 minutes to obtain phosphorylated pulp. After thoroughly washing the phosphorylated pulp, distilled water was added to prepare an aqueous suspension with a solid content of 1% by mass. A 1M sodium hydroxide solution was added to the aqueous suspension to obtain an aqueous suspension containing cellulose fibers with a pH of 12.5. The aqueous suspension was dehydrated and washed three times with distilled water, and distilled water was added to the cellulose fibers obtained after dehydration to obtain 1 kg of an aqueous suspension with a solid content of 0.75% by mass. The aqueous suspension was defibrated by passing it through a high-pressure homogenizer (ECONIZER LABO-02 manufactured by Sanmaru Machinery Co., Ltd.) a total of seven times at a pressure of 60 MPa to obtain an aqueous suspension of phosphorylated CNF. 26.7 g of the obtained aqueous suspension of phosphorylated CNF was diluted with distilled water to obtain 100 g of an aqueous suspension with a solid content of 0.2% by mass, and 0.1 M aqueous hydrochloric acid was added to the aqueous suspension to adjust the pH to 2.54. The pH and electrical conductivity were measured while dropping 0.1 M sodium hydroxide solution, and the electrical conductivity at each drop amount was plotted until the pH reached approximately 10. The amount of phosphate groups introduced was measured, which was 1.55 mmol / g. This confirmed that the modified cellulose substituted with phosphate groups was defibrated while remaining in its original state.
[0050] The fiber diameter and fiber length of the obtained phosphorylated CNF were measured in the same manner as in Sample 1. The fiber diameter was in the range of 3.8 to 9.9 nm, the number average fiber diameter was 5.6 nm, the fiber length was in the range of 487 nm to 1.22 μm, the number average fiber length was 854 nm, and the average aspect ratio was 153.
[0051] (Sample 4: TEMPO oxidized CNF) TEMPO-oxidized CNF was prepared as modified CNF according to the reference example of Japanese Patent No. 6668558, and an aqueous suspension of TEMPO-oxidized CNF with an average oxidation degree of 2 mmol / g was obtained. This CNF was defibrated as modified cellulose substituted with carboxyl groups. The fiber diameter and fiber length of the obtained TEMPO-oxidized CNF were measured in the same manner as for Sample 1. The fiber diameter was in the range of 3.7 to 7.9 nm, the number average fiber diameter was 6.3 nm, the fiber length was in the range of 513 nm to 1.31 μm, and the number average fiber length was 912 nm. The average aspect ratio was 143.
[0052] <Emulsion test> We attempted to emulsify the oily substances listed below. The organic and inorganic values of each oily substance are highly correlated with the hydrophilic and lipophilic properties in the HLB method, and when comparing the value calculated from the ratio of the organic value (OV) to the inorganic value (IV) [IV / OV = IOB (Inorganic Organic Balance)] with the HLB value, the approximate formula "HLB value = IOB value x 10" holds. Therefore, using this approximate formula, we calculated the HLB value of each oily substance. This value is also shown. Squalane (Kishida Chemical Co., Ltd.: 1st grade reagent) HLB value: 0 1-Decanol (Fujifilm Wako Pure Chemical Industries, Ltd.: 1st grade reagent) HLB value: 5 Limonene (Tokyo Chemical Industry Co., Ltd.: purity 95% or more) HLB value: 0.7 Silicone oil (Dow Toray Industries, Inc.: SRX310) HLB value: 1.7 Olive oil (Nacalai Tesque, Inc.: Chemical grade CP) HLB value: 1.6 Toluene (Kishida Chemical Co., Ltd.: special grade reagent) HLB value: 1.1 ·Ricinoleic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.: content 80% or more) ·HLB value: 7.0
[0053] <Measurement of the average particle size of oil droplets> The emulsion suspension obtained by the emulsification treatment was observed with a digital microscope (Keyence Corporation: VHX-6000) to measure the average particle size of the oil droplets.
[0054] <Evaluation of emulsification state> An accelerated emulsion stability test was performed by centrifuging 50 g of each emulsion suspension at 1,000 G for 15 minutes in a tabletop centrifuge (5200, manufactured by Kubota Shoji Co., Ltd.). The state of the emulsion suspension was then visually observed and judged according to the following criteria. 〇: An emulsion layer is formed and there is no oil separation ·△: A small amount of oil is floating ×: No emulsification and oil separation
[0055] (Example 1: Large amount of squalane added) In preparing the emulsified suspension, RCNF of Sample 1 was diluted with distilled water to a CNF concentration of 1.0 mass% to obtain 30 g of water suspension (CNF: 0.3 g). 20 g of squalane was added to this water suspension, and emulsified for 5 minutes at 8,000 rpm using a homogenizer (Excel Auto Homogenizer ED-4, manufactured by Nippon Seiki Seisakusho Co., Ltd.) to obtain an emulsified suspension. The amount of oily substance in the entire emulsified suspension was 40 mass%, and the addition rate of CNF was 0.60 mass%.
[0056] [Table 2]
[0057] In addition, when the average particle size of the oil droplets was measured for the emulsified suspension obtained in Example 1, it was confirmed that the oil droplets were dispersed as fine oil droplets of 10 to 30 μm. A photograph taken 4 weeks after obtaining this emulsified suspension is shown on the left side of Figure 2. The entire liquid was cloudy, and the emulsified state was maintained.
[0058] Example 2: 1-Decanol An emulsified suspension was obtained in the same manner as in Example 1, except that the aqueous suspension used was changed to 45 g of aqueous suspension (CNF: 0.135 g) diluted to a CNF concentration of 0.30 mass % and the oily substance was changed to 5 g of 1-decanol. The amount of the oily substance relative to the entire emulsion suspension was 10 mass %, and the addition rate of CNF was 0.27 mass %.
[0059] Example 3: Limonene An emulsified suspension was obtained in the same manner as in Example 1, except that the aqueous suspension used was changed to 45 g of aqueous suspension (CNF: 0.225 g) diluted to a CNF concentration of 0.50 mass % and the oily substance was changed to 5 g of limonene. The amount of the oily substance relative to the entire emulsion suspension was 10 mass %, and the addition rate of CNF was 0.45 mass %.
[0060] Example 4: Silicone Oil An emulsified suspension was obtained in the same manner as in Example 1, except that the aqueous suspension used was changed to 35 g of aqueous suspension (CNF: 0.175 g) diluted to a CNF concentration of 0.50 mass % and the oily substance was changed to 15 g of silicone oil. The amount of the oily substance relative to the entire emulsion suspension was 30 mass %, and the addition rate of CNF was 0.35 mass %.
[0061] (Example 5: Small amount of squalane added) An emulsified suspension was obtained in the same manner as in Example 1, except that the aqueous suspension used was changed to 40 g of aqueous suspension (CNF: 0.20 g) diluted to a CNF concentration of 0.50 mass % and the amount of squalane, an oily substance, was reduced to 10 g. The amount of the oily substance relative to the entire emulsion suspension was 20 mass %, and the addition rate of CNF was 0.40 mass %.
[0062] Example 6: Olive Oil An emulsified suspension was obtained in the same manner as in Example 1, except that the aqueous suspension used was changed to 40 g of aqueous suspension (CNF: 0.20 g) diluted to a CNF concentration of 0.30 mass % and the oily substance was changed to 10 g of olive oil. The amount of the oily substance relative to the entire emulsion suspension was 20 mass %, and the addition rate of CNF was 0.24 mass %.
[0063] (Example 7: Toluene) An emulsified suspension was obtained in the same manner as in Example 1, except that the aqueous suspension used was changed to 45 g of aqueous suspension (CNF: 0.225 g) diluted to a CNF concentration of 0.70 mass % and the oily substance was changed to 5 g of toluene. The amount of the oily substance relative to the entire emulsion suspension was 10 mass %, and the addition rate of CNF was 0.63 mass %.
[0064] Example 8: Ricinoleic acid An emulsified suspension was obtained in the same manner as in Example 1, except that the aqueous suspension used was changed to 45 g of aqueous suspension (CNF: 0.045 g) diluted to a CNF concentration of 0.10 mass % and the oily substance was changed to 5 g of ricinoleic acid. The amount of the oily substance relative to the entire emulsion suspension was 10 mass %, and the addition rate of CNF was 0.09 mass %.
[0065] (Reference example 1: Insufficient amount added) In Example 1, an emulsified suspension was obtained by the same procedure except that the aqueous suspension used was changed to 40 g of aqueous suspension (CNF: 0.040 g) diluted to a CNF concentration of 0.10 mass % and the oily substance was changed to 10 g of limonene, but some of the oily substance remained floating on the top of the mixture with the CNF aqueous suspension. The amount of the oily substance in the entire mixture was 20 mass %, and the CNF addition rate was 0.08 mass %. A photograph taken one week after obtaining this incomplete emulsified suspension is shown on the right side of Figure 2. The entire suspension was not completely emulsified, and the oily substance, including the partly emulsified one, gathered at the top and separated.
[0066] (Reference example 2: Insufficient amount added) In Example 1, an emulsified suspension was obtained by the same procedure except that the aqueous suspension used was changed to 35 g of aqueous suspension (CNF: 0.035 g) diluted to a CNF concentration of 0.10 mass % and the oily substance was changed to 15 g of squalane, but it was not possible to emulsify all of the oily substance, and some of it remained separated. The amount of the oily substance in the entire mixture was 30 mass %, and the addition rate of CNF was 0.07 mass %.
[0067] (Comparative Example 1: Olive oil and mechanically defibrated CNF) In Example 6, the CNF used was changed to the mechanically defibrated CNF of Sample 2, the CNF concentration was kept at 0.30% by mass, the amount of the water suspension was increased to 45 g (CNF: 0.45 g), and the amount of olive oil was reduced to 5 g. An attempt was made to obtain an emulsified suspension by the same procedure, but the oily substance was not emulsified at all and remained separated. The amount of oily substance relative to the entire mixture was 10% by mass, and the addition rate of mechanically defibrated CNF was 0.27% by mass. In other words, even if the amount of oily substance was reduced by using mechanically defibrated CNF with a larger amount of addition than the CNF of Example 6, it was not possible to completely emulsify all of the oily substance.
[0068] (Comparative Example 2: 1-decanol-phosphorylated CNF) In Example 2, an emulsified suspension was obtained by following the same procedure, except that the CNF used was changed to the phosphorylated CNF of Sample 3. Although some of the mixture was emulsified, a small amount of the oily substance remained floating on the top of the mixture. The amount of the oily substance in the entire mixture was 10% by mass, and the amount of phosphorylated CNF added was 0.27% by mass.
[0069] (Comparative Example 3: Ricinoleic acid / phosphorylated CNF) In Example 8, the CNF used was changed to phosphorylated CNF of Sample 3, the CNF concentration was increased to 0.30% by mass to increase the CNF content in 40 g of the aqueous suspension (CNF: 0.12 g), and the amount of ricinoleic acid used as the oily substance was increased to 10 g. An attempt was made to obtain an emulsified suspension by the same procedure, but all of the oily substance could not be emulsified, and some of it remained separated. The amount of oily substance relative to the entire mixture was 20% by mass, which was twice that of Example 8, and the addition rate of phosphorylated CNF was 0.24% by mass, which is more than twice that of Example 8. Although the ratio of CNF to oily substance was higher than that of Example 8, all of the oily substance could not be emulsified.
[0070] (Comparative Example 4: Olive oil and TEMPO oxidized CNF) In Example 6, the CNF used was changed to the TEMPO-oxidized CNF of Sample 4, the CNF concentration was kept at 0.30% by mass, the amount of the water suspension was increased to 45 g (CNF: 0.135 g), and the amount of olive oil (oil-based substance) was reduced to half, 5 g, in an attempt to obtain an emulsified suspension by following the same procedure, but some of the oil-based substance remained floating on the top of the mixture in small amounts. The amount of the oil-based substance in this entire mixture was 10% by mass, and the addition rate of TEMPO-oxidized CNF was 0.27% by mass.
[0071] (Comparative Example 5: Limonene-TEMPO oxidation) An attempt was made to obtain an emulsified suspension using the same procedure as in Example 3, except that the CNF used was changed to the TEMPO-oxidized CNF of Sample 4; however, it was not possible to completely emulsify all of the oily substance, and some of it remained separated.
[0072] (Consideration) By using the unmodified CNF of the present invention, as shown in Examples 1 to 8, it was possible to produce emulsion suspensions in which oil droplets of approximately 10 to 30 μm were emulsified and dispersed in water for a wide range of oily substances with HLB values of 0 to 7.0 without using a separate surfactant.
[0073] On the other hand, in Reference Examples 1 and 2, in which unmodified CNF was used but the amount of CNF added was small and the amount of oily substance was more than 200 times by mass, there was a relative lack of CNF surrounding the surface of the oily substance, making it impossible to stably fix it, and the emulsified state was evaluated as △ and ×, respectively.
[0074] In addition, in Comparative Example 1, which used mechanically defibrated CNF with a large fiber diameter, the oil droplets became large and the oily substance could not be completely emulsified. Furthermore, in Comparative Examples 2 and 3, which used phosphorylated CNF, and Comparative Examples 4 and 5, which used TEMPO-oxidized CNF, the amount of CNF was sufficient compared to the examples, but the evaluation of the emulsification state was not good in either case. In addition, in these modified CNFs, the emulsification state differed slightly depending on the type of oily substance used, suggesting a difference in the interaction between the functional groups of the modified CNF and the oily substance.
[0075] <Oil droplet confirmation test> When the emulsion suspension obtained in Example 1 was observed under polarized light with the digital microscope, it was confirmed that the cellulose, which appeared shiny, was concentrated around the oil droplets and maintained a state of being adsorbed to the oil droplets at the liquid-liquid interface. The digital microscope photographs are shown in Figures 3(a) and (b).
Claims
1. An oil-in-water emulsifier comprising unmodified cellulose nanofibers having an average fiber diameter of 3 nm or more and 10 nm or less.
2. The oil-in-water emulsifier according to claim 1 , wherein the unmodified cellulose nanofiber is unmodified cellulose regenerated from modified cellulose.
3. A method for producing an emulsified suspension, comprising dispersing oil droplets in water using the oil-in-water emulsifier according to claim 1 or 2.
4. 3. An emulsified suspension comprising oil droplets dispersed in water using the oil-in-water emulsifier according to claim 1 or 2.
Citation Information
Patent Citations
Optical branching circuit
JP1988060408A
Water-in-oil type emulsion composition and cosmetic
JP2006342140A
Emulsification composition, cosmetic composition, and method for producing emulsified composition
JP2021059502A
Oil-in-water emulsifier and cosmetic
JP7220088B2